Дiяльнiсть осередкiв товариства «Просвіта» в селах Грабове та Сереховичi Ковельського повiту на Волині (20–30-ті рр. ХХ ст.) - Сущук, Оксана; Susuk, Oksana (My University, 2016)
У статті всебічно досліджено, проаналізовано та узагальнено процес становлення й особливості діяльності сільських осередків товариства «Просвіта» на територiї Ковельського повiту та на прикладi вивчення icторiї просвiтянських гурткiв сiл Cерeховичi й Грабове зʼясовано їх внесок у національно-культурне відродження регiону y 20–30-x рр. ХХ ст.The article comprehensively examines the development of educational movement in the territory Kovalskogo County of Volyn province in the 20-30-ies of XX St. and summarizes the process of formation and features of the rural cell of the society «Prosvita». The author analyzes the Charter of a district society, directions and methods of work and organizational documents of the subsidiaries, explores their relationship with the County organization, said relations grass-roots local organizations with the authorities the Polish authorities.
The Activity of the Cells of the Society «Prosvita» in the Villages Hornbeam and Terehovich Kovel District in Volhynia (20-30-ies of the XXth Century)
Keywords: просвітянський рух; польська влада; товариство «Просвіта»; educational movement; the Polish government; society «Prosvita»; educational center; circle; national- cultural revival